PRINCIPLES OF DESIGN OF ADVERTISING PRODUCTS AS A MEANS OF COMMUNICATION - Nyshta , Diana; Kvasnytsia , Roksoliana (Collection of scientific papers «ΛΌГOΣ», 2024)
Today, the topic of ecology is an acute one, so the development of design principles and tools aimed at raising the environmental awareness of children and adolescents is relevant. There is a growing need to develop environmental awareness in children and adolescents through a combination of visualizations of various advertising products, such as posters, brochures, illustrations and interactive technologies. Therefore, there is a growing need to formulate principles and tools in the design of advertising products that will direct advertising to educate eco consciousness.